Analisis Penjualan Baju Seragam Sekolah di Konveksi Hanifah Collection - Fazarudin, Ahmad; Nalhadi, Ahmad; Dwiputra, Gerry Anugrah (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
Hanifah Collection is a company engaged in the convection of school uniforms. The fluctuating number of requests each month creates its problems in determining the amount of production. This study aims to find a method that matches the data pattern as the basis for determining the amount of output in the next period. The technique used in this study is the forecasting method of Moving Average, Exponential Smoothing and Triple Exponential Smoothing with parameter level errors of each way using MAD, MSE, and MAPE. From the results of this study, there is a moving average method with the most appropriate method in determining demand forecasting in the next period with a value of MAD of 172.22, MSE of 46624.34 and MAPE 46624.34.